Operation Characteristics of Mechanical DC Circuit Breaker Combined with LC Divergence Oscillation Circuit for High Reliability of LVDC System - Sang-Yong Park; Hyo-Sang Choi (Energies, 2021)
DC systems are modernly starting to come into the spotlight again due to the carbon-neutral policy, the development of semiconductor devices for power, and the increase in digital loads. We need to prepare in advance solutions to problems that may arise from fault currents due to transients for future DC power grid models. In the case of DC, there is no current zero-point because there is no frequency. Therefore, a large switching surge is generated when the circuit breaker cuts off the fault current. The possibility of insulation breakdown is greater than that of AC in severe cases. We consider power semiconductors or superconducting current limiters as an alternative. However, DC breaking cannot be safely achieved by itself. For reliable DC breaking, mechanical circuit breakers must be used with them. Among the mechanical shut-off methods, we adopted the divergence oscillation method. It has the biggest advantage compared to other methods in that it has a simple structure by composing passive elements and can artificially create zero current. In addition, it can be applied to a power semiconductor and a superconducting current limiter to perform a high-reliability cut-off operation. In this paper, we conducted simulation analysis by configuring the DC power grid and DC cut-off system through the PSCAD/EMTDC program. Results confirmed that the application of the LC divergence oscillation circuit can reduce the cut-off time and reduce the power burden of the mechanical DC circuit breaker (MCB).